2013
DOI: 10.4028/www.scientific.net/amm.471.349
|View full text |Cite
|
Sign up to set email alerts
|

Translation to Rotary Frequency-Up Conversion Vibration Based Energy Harvesting Device for Human Body Motion

Abstract: This paper presents some preliminary studies on the frequency-up conversion method for low frequency application energy vibration based harvesting device, mainly from human body motion, by employing the translation to rotary mechanism. Vibration signals from different parts of the human body were first measured when the human subject was walking at 5 km/h. The signals obtained from the measurement were then reconstructed using Fourier Transform and it was found that frequency content of human body motion was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The oscillation of external force has a frequency of 2 Hz and amplitude of 1 m•s −2 , which corresponds to the vibration in human walking. 38) The output power is calculated from P ¼ v 2 =R l , where R l is set to get impedance matching between R l and C p . Figure 1(a) shows the mechanical potential energy of the nonlinear pVEHs with hardening and softening springs and linear pVEH as a function of the amplitude of the displacement of the proof mass.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oscillation of external force has a frequency of 2 Hz and amplitude of 1 m•s −2 , which corresponds to the vibration in human walking. 38) The output power is calculated from P ¼ v 2 =R l , where R l is set to get impedance matching between R l and C p . Figure 1(a) shows the mechanical potential energy of the nonlinear pVEHs with hardening and softening springs and linear pVEH as a function of the amplitude of the displacement of the proof mass.…”
Section: Resultsmentioning
confidence: 99%
“…The human motion vibration consists of multiple oscillations with different frequency and acceleration. 38) Moreover, Beeby et al reported that softening nonlinear VEHs can generate the electrical power effectively when the multiple oscillations exist in their bandwidth. 30) Therefore, the response of linear and hardening pVEHs to a combined vibration, which consists of a fundamental deterministic vibration and a second vibration, is analyzed numerically, because the second vibration is not sub-harmonics or superharmonics of the resonant frequency of the pVEHs, which is not suitable for harmonic balance method.…”
Section: Resultsmentioning
confidence: 99%
“…The vibration amplitude and frequency are quite various and random in different environments. For the vibration excited by ocean waves or the body movements of humans, it has characteristics of low frequency and high swinging amplitude [ 32 , 33 ], which indicates that the energy harvester should have a low working frequency and wide frequency range to harvest the vibration energy in these scenes. According to the working principle of a transducer, the types of vibrational energy harvester can be divided into electrostatic, piezoelectric, and electromagnetic [ 34 ].…”
Section: Introductionmentioning
confidence: 99%